How "Peasant Apartments" Could Undermine Rural Governance in China: Spatial Realignment, Moral Reconfiguration and Local Authority. (11th June 2020) - Yep, Ray; Wu, Ying
Abstract: A seismic change in the residential pattern is emerging in rural China today: traditional rural houses have been rapidly erased from the face of the countryside with large numbers of peasants being relocated to modern high-rise buildings. This process of "peasant elevation" has had a monumental impact on rural China. It redefines the entitlement to land use by the rural citizenry and negotiations for a new regime of property rights concerning land administration, while, most importantly, it undermines the position of the local state in rural China, whose authority is an aggregation of three distinctive elements: coercive power inherent in the state apparatus, control over economic resources, and resonance with local morality. Based on original data collected in Chongqing, Nantong and Dezhou, this paper argues that the comprehensive uprooting of the Chinese peasantry from the land and the resulting complications have caused moral disorientation among the relocated peasants and fragmentation of local authority. The difficulty in establishing community identity in the new setting has further undermined local governance. This may in turn trigger a wave of social and political tensions that may eventually turn out to be a major political challenge to the regime for years to come.